Effectiveness of Interventions for English Learners with Word Reading Difficulties: A Research Synthesis. Issue 3 (24th August 2022) - Solari, Emily J.; Kehoe, Karen F.; Cho, Eunsoo; Hall, Colby; Vargas, Isabel; Dahl‐Leonard, Katlynn; Richmond, Cassidi L.; Henry, Alyssa R.; Cook, Lysandra; Hayes, Latisha; Conner, Carlin
Abstract: This study meta‐analyzed the last four decades (1980–2020) of reading intervention research focused on improving reading outcomes for English language (EL) students in Grades K–5 with or at risk for word reading difficulties. Experimental and quasi‐experimental group design and single‐case experimental design (SCED) studies were included; 10 group design and 7 SCED studies met inclusion criteria ( m = 61; total student N = 2, 270). Visual inspection of the effect size distribution revealed that the assumption of between‐study heterogeneity was not supported; therefore, the findings were synthesized for SCED studies separately from those reported in group design studies. Implications for practice, policy, and future research are discussed.